Branching Under the Influence of Substances Growing The "Napoleon" and “Kora Gilos” Varieties of Cherries in Vitro Conditions. - Abduramanova Salamat Khudaybergenovna; Islamov Sahib Yakshabekovich (Genius Journals, 2023)
The article lists the varietal branching ratio and branch elongation indicators for microclonal branching of cherry varieties under the influence of MS, DKW, and MSTAK in nutrient media under in vitro conditions BAP-0.30, 1.0 mg/l, TDZ – 0.50, 1.0, and MetP - 0.20, 0.30, 0.50, and 1.0 mg/L.
Keywords: Cherry; nutrient medium; explant; growing material